ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI PAJAK DAERAH (Studi Kasus Pada Kota Dan Kabupaten Di Propinsi Jawa Tengah Tahun 2009 - 2014) - Easy Natalia, 08.05.52.0017; Maryono, Maryono (Students' Journal of Accounting and Banking, 2016)
This research is a study that evaluated the effects are affecting reception Regional Tax on city and regency in Central Java Province . Local Tax is one source of local revenue for carrying out local development . Each year the amount of local taxes in each of the City and County of fluctuation. Thus , the authors are interested in researching more about the influence of Total Population , income per capita , the number of tourists , and Number of Awards to Local Tax receipts in the city and regency in Central Java Province. In this study, the data collection is done by documentation, which collects records / data required under the research to be conducted from the office / offices / agencies or institutions (Suharsimi Arikunto, 2002). Reports related to tax income relating to the area of population, income per capita, the number of tourists, and the number of hotels. Secondary data were obtained from official documents issued by relevant authorities. The results of research and discussion obtained, that the coefficient of determination in this study was obtained by the value of Adjusted R Square of 0.822 which means that 82.2% of local tax variation influenced by variables of population, income per capita, the number of tourists and the number of hotels. While the remaining 17.8% of the variation of local taxes can be affected by other variables.Keywords: Local Taxes, Total Population, income Per Capita, The Number Of Tourists, Population